Wind-stress feedback amplification of abrupt millennial-scale climate changes - Arzel, Olivier; England, Matthew H. (Climate Dynamics, 2013)
International audience The influence of changes in surface wind-stress on the properties (amplitude and period) and domain of existence of thermohaline millennial oscillations is studied by means of a coupled model of intermediate complexity set up in an idealized spherical sector geometry of the Atlantic basin. Using the atmospheric CO2 concentration as the control parameter, bifurcation diagrams of the model are built to show that the influence of wind-stress changes on glacial abrupt variability is threefold. First, millennial-scale oscillations are significantly amplified through wind-feedback-induced changes in both northern sea ice export and oceanic heat transport. Changes in surface wind-stress more than double the amplitude of the strong warming events that punctuate glacial abrupt variability obtained under prescribed winds in the model. Second, the average duration of both stadials and interstadials is significantly lengthened and the temporal structure of observed variability is better captured under interactive winds. Third, the generation of millennial-scale oscillations is shown to occur for significantly colder climates when wind-stress feedback is enabled. This behaviour results from the strengthening of the negative temperature-advection feedback associated with stronger northward oceanic heat transport under interactive winds.